Fintech and banks collaboration: Does it influence efficiency in the banking sector? - Davis Bundi Ntwiga (Kenya Bankers Association (KBA), 2020)
This Efficient banks increase financial stability, intermediation and value to the shareholders. As Fintech innovations continue to alter the landscape in the banking sector in Kenya, the collaboration between Fintech and bank will continue to shape the evolution of credit allocation and delivery of services. This study investigates if Fintech and bank collaboration have a negative or positive influence on efficiency in the banking sector. The data envelopment analysis is applied with input-orientation based on four intermediation dimension models. Efficiency scores are decomposed into technical efficiency, pure technical efficiency and scale efficiency. Financial statement data from 2009-2018 for top 15 banks based on the market share of which 13 banks are either locally owned or Nairobi Securities Exchange-listed, with 2 foreign-owned banks excluded from the study. Among these two categories, 5 banks have Fintech collaborations. The study period is segmented into Pre-Fintech, 2009-2014 and Post Fintech, 2015-2018. Descriptive statistics summarize the data, Kruskall Wallis and Conover tests for the Post-Hoc with Panel regression model testing the effect of financial ratios on technical efficiency of banks for Pre-Post Fintech period. Fintech collaborating banks had superior management performance and higher efficiency scores in Pre-Fintech and Post Fintech compared to the NSE listed and locally owned banks based on model M4. Fintech collaboration significantly reduced the cost of intermediation, and increased the scale of operations, a decrease in returns to scale. Therefore, Fintech and banks collaborations had a positive effect on efficiency in the banking sector but it is not statistically significant.
Keywords: 330; Collaboration; Efficiency; Banks; Fintech; Technical; and Data Envelopment Analysis